Women directors involvement in Malaysia - Amran, Noor Afza; Ku Ismail, Ku Nor Izah; Aripin, Norhani; Hassan, Norlaili; Abd Manaf, Kamarul Bahrain; Abdullah , Shamsul Nahar (INSI Publications, 2014)
Empirical studies found that women are under-represented on corporate boards despite their high participation in the workforce. In Malaysia, the establishment of Ministry of Women, Family and Community Development plays a role in boosting the women roles. In year 2004, the Malaysian Government has imposed the public sector agencies to appoint 30% women to be involved at the decision making levels. In 2011, the government extended the policy to the private sector and set 2016 as the year for meeting the target. This paper seeks to determine the level of women participation on boards in 2010 and examine the profiles of the women, as well as the companies that appoint women to their boards. Based on 831 Malaysian listed companies, we find that a majority of women directors are of Chinese ethnicity, non-independent directors, and have an accounting and other business-related academic background. Many of them are family-related to other directors. This study contributes significantly to the policy makers and the authority responsible for promoting women to become directors.